Policy changes and its enforcement toward foreign workers in hotel industry - Ahmad, Rozila; Abdul Rahman, Rohana; Mustaffa, Che Su; Mohd Shariff, Nurhazani; Zainol, Noor Azimin; Rashid Radha, Jasmine Zea Raziah Radha (GLOBAL ACADEMIC EXCELLENCE (M) SDN BHD, 2020)
The change of government after the 14th Malaysian general election is followed by some changes in government policies and practices. Hence, business practices including those in the service industry are also affected. Among the issues raised in the Dewan Rakyat is regarding the employment of foreign labour. While the news has broadcasted information regarding efforts to reduce the number of foreign workers in Malaysia under the new government, scholarly article regarding the matter remains scarce. This paper tracks the current policies on foreign workers and their enforcement effort. Findings from secondary data reveal that there are some changes in policies that regulate foreign workers’ employment, and there is stricter enforcement of the regulations. While the local employees can rest assured that there will be fewer competition for jobs, it is also crucial for them to improve their attitude and increase their productivity.